Developing the EPI Symptom Questionnaire (EPI-SQ): a qualitative study to understand the symptom experience of patients with exocrine pancreatic insufficiency (EPI) - Sally Mannix; Amit Bodhani; Leah Kleinman; Nikhil Khandelwal; Vikesh K. Singh (SpringerOpen, 2024)
Abstract Background Symptom assessment is the key factor in determining disease status and optimal management of exocrine pancreatic insufficiency (EPI). There is a need for a standardized patient-reported outcome (PRO) questionnaire to assess symptoms in patients diagnosed with EPI. The purpose of this qualitative study was to increase understanding of the EPI symptom experience from the patients' perspective, and to develop and evaluate the content validity of the EPI Symptom Questionnaire (EPI-SQ) in US patients with EPI. Methods Concept elicitation interviews (Phase I) were conducted to understand the symptom experience in patients with a clinical diagnosis of EPI (i.e., fecal pancreatic elastase value of ≤ 200 mcg/g based on most recent value) due to chronic pancreatitis or pancreatectomy. The EPI-SQ was developed based on the data extracted from Phase I interviews and feedback from clinical experts. Next, separate cognitive interviews (Phase II) were conducted to evaluate participants' understanding of the instructions, items, response scales, and recall periods of the instrument. Results During Phase I interviews (n = 21), 19 participants (90%) reported abdominal pain as the most frequent EPI symptom and lifestyle changes were the most frequently endorsed impacts (n = 18; 86%). Phase II results indicated that all participants (n = 7) felt the 12-item EPI-SQ was relevant to their symptom experience and that they understood the items, instructions, and response options as intended. Conclusion The qualitative data from this study support the content validity of the EPI-SQ in measuring EPI symptom severity in US patient populations diagnosed with EPI.